The Effect of Decyl Glucoside on Stability and Irritability of Nanostructured Lipid Carriers-Green Tea Extract as Topical Preparations - Rufaidah Azzahrah; Noorma Rosita; Djoko Agus Purwanto; Widji Soeratri (Jurnal Farmasi dan Ilmu Kefarmasian Indonesia)
Background: Green Tea Extract (GTE) is a natural antioxidant compound that can protect the skin from photocarcinogenesis (DNA damage due to ultraviolet exposure). GTE has low stability, which needs a delivery system such as Nanostructured Lipid Carriers (NLC) with decyl glucoside (DG) as a natural surfactant that at the right concentration can produce a significantly small particle size which can improve the stability of the NLC. Objective: To determine the effect of DG usage on the characteristics, physical stability, and irritability of NLC-GTE preparation. Methods: NLC-GTE preparation used the High Shear Homogenization (HSH) method with three formulas, which contained DG 2%, 2.5%, and 3% consecutively. Afterwards, the characteristic and physical stability tests were conducted using the thermal cycling method for three cycles with two different temperatures (48 hours/cycle, 2 - 8°C and 40°C). The irritability test used Hen's Egg Test on the Chorioallantoic Membrane (HET-CAM) method. Results: Characteristic test of organoleptic showed that all formulas were white, odorless, and had a semi-solid consistency. However, the pH, particle size, and polydispersity index values from all formulas were within the normal range of values. The physical stability test result showed that 3% DG was the most stable formula. This formula was within the non-irritating range of values in HET-CAM. Conclusion: NLC-GTE with an increased concentration of DG as a surfactant can improve the characteristics and physical stability of the preparation. F3 (3% DG) is the best formula compared to other formulas and indicates non-irritating in the HET-CAM test.